Mental Health Literacy Levels of Medical Staff in China: An Assessment Based on a Meta-Analysis - Guo, Shengyu; Xiong, Jie; Liu, Feiyue; Su, Yanlin (Frontiers in Psychiatry, 2021)
Abstract Background: The awareness rate of mental health knowledge among medical staff is an important evaluation index to assess the mental health service capacity of a country or region, and the mental health knowledge of medical staff in China have not been quantitative evaluated. Study Design: This study systematically combined pertinent quantitative study data from previous related studies to conclude the awareness rate of mental health knowledge among Chinese medical staff Methods: Related studies from 5 electronic databases were searched, a meta-analysis was conducted to obtain the combined result. The Primary outcome of the present study was the awareness rate of medical staff or the sample size and the number those who can answer the relevant questions correctly. We also performed a hierarchical analysis according to the sample group's region and specialty. The awareness rate of medical staff and corresponding 95% confidence intervals (CIs) were calculated. The heterogeneity was assessed with I2 test, and Egger’s test was used to evaluate publication bias. Results: A total of 15 articles with 11526 medical staff were included in the present study, the overall awareness rate of mental health knowledge among Chinese medical staff was as low as 0.81. The awareness rate of mental health knowledge among medical workers in developed regions is higher than that in developing regions. The awareness rate of mental health among medical staff in department of psychiatry , nonpsychiatry and community medical staff was 88%, 68%, 82%, respectively. Conclusions: The overall awareness rate among medical staff in this country are low, and the awareness rate in developed regions is higher than medical staff in developing regions. Psychiatric hospital staff has a higher awareness rate compared to community medical staff, nonpsychiatric hospital staff has the lowest awareness rate. Key words: awareness rate, medical staff, mental health knowledge, meta-analysis Abbreviations: log: logarithmic transformation of the original rate, logit: perform logit conversion to the original rate, Arcsin: inverse sine transform of the original rate, Darcsin: Freeman-Tukey double inverse sine conversion of the original rat